Digital transformation and productivity trends: the new paradox - Jona-Lasinio, Cecilia (Henry Stewart Talks, 2022)
Tangibles and intangibles, Innovation, Digital economies, Productivity slowdown, Business models, Economy, Labor, TFP growth